Culinary and Souvenir Center in Pematangsiantar City with Neo-Vernacular Architecture Approach - Rachmawati, Sara Vaneza; Ginting, Nurlisa (Jurnal Koridor, 2024)
Tourists often look for authentic culinary experiences and want to bring home typical souvenirs from the places they visit. Pematangsiantar City, North Sumatra, which is a passageway city for tourists who want to visit Lake Toba, has a variety of culinary and souvenir options. The purpose of this research is to design a culinary and souvenir center in Pematangsiantar City with a neo-vernacular architectural approach. The method used in this design is a qualitative method through literature studies, field studies, and comparative studies that produce space requirements and criteria that will be used as the basis for the design. The results of this research will be the basis for designing a building complex with food stands, souvenir stands, eating and drinking areas, and public open spaces. The whole project is expected to improve the local economy, promote sustainable tourism, and strengthen the cultural identity of Pematangsiantar City.